(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze some factors affecting malaria surveillance and prevention activities in Khanh Vinh area, Khanh Hoa province in 2023-2024. Methods: A cross-sectional study combining quantitative and qualitative approaches was conducted. Results: The number of malaria cases decreased from 196 in 2023 to 184 in 2024, mainly among the 5-15-year-old age group, with no reported deaths. More than 90% of the population was protected by insecticide-treated bed nets, and medical supplies and drugs were adequately provided. However, severe malaria cases increased from 1 to 19, and Plasmodium falciparum accounted for 48.9% of infections in 2024. Positive influencing factors included: comprehensive technical guidance, adequate human resources, and well-equipped basic infrastructure. Negative influencing factors included: uncontrolled migration, sleeping in fields without bed nets, self-medication, low education and income levels, deteriorated equipment, poor internet connectivity, limited funding, and mountainous terrain favorable for mosquito breeding. Recommendations: Reassess malaria hotspot areas, conduct training on severe malaria diagnosis, develop multilingual health communication, and upgrade information technology infrastructure; establish malaria risk maps, strengthen parasite surveillance and monitor bed net use; enhance management of forest goers and field sleepers, collaborate with schools, and implement communication campaigns in ethnic minority languages.